Nuclear factor of activated T cells (NFATc4) is required for BDNF-dependent survival of adult-born neurons and spatial memory formation in the hippocampus - Giorgia Quadrato; Marco Benevento; Stefanie Alber; Carolin Jacob; Elisa M. Floriddia; Tuan Nguyen; Mohamed Y. El‐Naggar; Christine M. Pedroarena; Jeffery D. Molkentin; Simone Di Giovanni (2012)
New neurons generated in the adult dentate gyrus are constantly integrated into the hippocampal circuitry and activated during encoding and recall of new memories. Despite identification of extracellular signals that regulate survival and integration of adult-born neurons such as neurotrophins and neurotransmitters, the nature of the intracellular modulators required to transduce those signals remains elusive. Here, we provide evidence of the expression and transcriptional activity of nuclear factor of activated T cell c4 (NFATc4) in hippocampal progenitor cells. We show that NFATc4 calcineurin-dependent activity is required selectively for survival of adult-born neurons in response to BDNF signaling. Indeed, cyclosporin A injection and stereotaxic delivery of the BDNF scavenger TrkB-Fc in the mouse dentate gyrus reduce the survival of hippocampal adult-born neurons in wild-type but not in NFATc4 −/− mice and do not affect the net rate of neural precursor proliferation and their fate commitment. Furthermore, associated with the reduced survival of adult-born neurons, the absence of NFATc4 leads to selective defects in LTP and in the encoding of hippocampal-dependent spatial memories. Thus, our data demonstrate that NFATc4 is essential in the regulation of adult hippocampal neurogenesis and identify NFATc4 as a central player of BDNF–driven prosurvival signaling in hippocampal adult-born neurons.